Optimal Synthesis and Application of a Si–Ti–Al Ternary Alloy as an Anode Material for Lithium-Ion Batteries - Jaehan Lee (MDPI AG, 2021)
The development of novel anode materials for high energy density is required. Alloying Si with other metals is a promising approach to utilize the high capacity of Si. In this work, we optimized the composition of a Si–Ti–Al ternary alloy to achieve excellent electrochemical performance in terms of capacity, cyclability, and rate capability. The detailed internal structures of the alloys were characterized through their atomic compositions and diffraction patterns. The lithiation process of the alloy was monitored using real-time scanning electron microscopy, revealing that the mechanical stability of the optimized alloy was strongly enhanced compared to that of the pure silicon material.